2020
DOI: 10.1021/acs.jpclett.0c01574
|View full text |Cite
|
Sign up to set email alerts
|

Striking Generic Impact of Light-Induced Non-Adiabaticity in Polyatomic Molecules

Abstract: Nonadiabaticity, i.e., the effect of mixing electronic states by nuclear motion, is a central phenomenon in molecular science. The strongest nonadiabatic effects arise due to the presence of conical intersections of electronic energy surfaces. These intersections are abundant in polyatomic molecules. Laser light can induce in a controlled manner new conical intersections, called light-induced conical intersections, which lead to strong nonadiabatic effects similar to those of the natural conical intersections.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…Our showcase example is the four-atomic H 2 CO (formaldehyde) molecule which has been investigated very recently for nonadiabatic phenomena induced by classical light. 26 This molecule does not exhibit any inherent nonadiabatic effects in the studied region of the nuclear conguration space (see further explanation in ESI †). Therefore, nonadiabatic effects appearing in the absorption spectrum of H 2 CO coupled to a single cavity mode can be attributed solely to the quantum LICI.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Our showcase example is the four-atomic H 2 CO (formaldehyde) molecule which has been investigated very recently for nonadiabatic phenomena induced by classical light. 26 This molecule does not exhibit any inherent nonadiabatic effects in the studied region of the nuclear conguration space (see further explanation in ESI †). Therefore, nonadiabatic effects appearing in the absorption spectrum of H 2 CO coupled to a single cavity mode can be attributed solely to the quantum LICI.…”
Section: Introductionmentioning
confidence: 94%
“…Moreover, LICIs are ubiquitous and become multidimensional in the nuclear coordinate space in polyatomic molecules due to the presence of several vibrational dofs. 25,26 Recently, efforts have been made to study light-induced nonadiabatic phenomena in optical or microwave cavities. [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] It has been successfully demonstrated that describing the photon-matter interaction with the tools of cavity quantum electrodynamics (cQED) [47][48][49][50] can provide an alternative way to study the quantum control of molecules with light.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then the coupling is zero and the molecule dissociates, while some population may be transferred to the ground potential by non-adiabatic processes in the vicinity of θ = π/2. In the representation of the LIPs, this process can be seen as fast internal conversion through a light-induced conical intersection 35–41 or LICI, using the language of Photochemistry, and it is possible even in diatomic molecules, including the rotational degree of freedom. There have been a plethora of studies concerning how to probe the LICIs and how to use them as a resource to control photochemical or photophysical processes, but if anything, one expects that the presence of LICIs will make it harder to stabilize the excited states of single electron molecules.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to natural CIs in field-free polyatomic molecules, the energetic and spatial position of LICIs can be controlled by varying the parameters of the laser field or cavity. The former case (classical laser light) has already been discussed several times, mainly in diatomics, [24][25][26][27] but in some situations in polyatomic molecules [28][29][30] as well, both theoretically [24][25][26][27][28][29][30] and experimentally. [31][32][33] However, the literature on the merits of the latter area…”
Section: Introductionmentioning
confidence: 99%